2020
DOI: 10.1001/jamapsychiatry.2020.0927
|View full text |Cite
|
Sign up to set email alerts
|

Association of Naturalistic Administration of Cannabis Flower and Concentrates With Intoxication and Impairment

Abstract: IMPORTANCEThe rapidly growing legal cannabis market includes new and highly potent products, the effects of which, to our knowledge, have not previously been examined in biobehavioral research studies because of federal restrictions on cannabis research. OBJECTIVE To use federally compatible, observational methods to study high-Δ9tetrahydrocannabinol (THC) legal market forms of cannabis. DESIGN, SETTING, AND PARTICIPANTSIn this cohort study with a between-groups design that was conducted in a community and uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(108 citation statements)
references
References 59 publications
6
87
2
Order By: Relevance
“…In our group's recent study among individuals who were frequent users of legal market flower and concentrated cannabis, we demonstrated that these participants showed tolerance such that acute cannabis use did not impact many cognitive tasks (e.g., inhibitory control and working memory). However, balance performance emerged as one psychomotor function that is impaired after acute use but appears to recover within 1 h. 22 These findings are among the only data on the acute cognitive and psychomotor effects of legal market forms of cannabis among regular users and need to be explored further using additional tasks and in other populations. Taken together, the existing literature underscores the importance of gaining a better understanding of the extent and time course of the effects of various cannabis preparations and THC concentrations on psychomotor tasks, balance, and cognition, all of which may adversely affect driving ability.…”
Section: Introductionmentioning
confidence: 98%
“…In our group's recent study among individuals who were frequent users of legal market flower and concentrated cannabis, we demonstrated that these participants showed tolerance such that acute cannabis use did not impact many cognitive tasks (e.g., inhibitory control and working memory). However, balance performance emerged as one psychomotor function that is impaired after acute use but appears to recover within 1 h. 22 These findings are among the only data on the acute cognitive and psychomotor effects of legal market forms of cannabis among regular users and need to be explored further using additional tasks and in other populations. Taken together, the existing literature underscores the importance of gaining a better understanding of the extent and time course of the effects of various cannabis preparations and THC concentrations on psychomotor tasks, balance, and cognition, all of which may adversely affect driving ability.…”
Section: Introductionmentioning
confidence: 98%
“…The only other verbal memory test included was the International Shopping List Task (ISLT), which used different words than the recognition task. Our larger study found that THC administration was negatively associated with ISLT performance, but CBD results await ongoing data collection and analysis (Bidwell et al 2020). 2 We do not have the specific time point for the memory assessment for each participant, so the time given here is an estimate based on the general flow of the protocol.…”
Section: Methodsmentioning
confidence: 76%
“…Second, the 50 min that elapsed after consumption prior to the memory assessment (which occurred~35 min after blood draw to assess peak cannabinoid levels) may have limited the observed effects of THC and CBD. On the other hand, we have found the effects of THC on verbal recall memory to be relatively persistent when international shopping list test (ISLT) performance was compared between 15 and 30 min after use versus 60-75 min after use (Bidwell et al 2020). Third, given the nature of this observational pilot study we were not powered to include all relevant covariates or ethically able to match the groups on important characteristics such as cannabis use history, preferred form of cannabis (e.g.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations